The safety and efficacy of esketamine in comparison to dexmedetomidine during drug-induced sleep endoscopy in children with obstructive sleep apnea hypopnea syndrome: A randomized, controlled and prospective clinical trial - Yongping, Zheng; Xinyi, Li; Aming, Sang; Qiang, Xie; Tianqi, Zhou; Mengmeng, Shen; Xiong, Chen; Xuemin, Song (Frontiers in Pharmacology, 2022)
Background and Purpose: Data and high-quality studies of anesthetic methods for children with obstructive sleep apnea hypopnea syndrome (OSAHS) who undergo drug induced sleep endoscopy (DISE) are limited. Few research on pediatric DISE using esketamine has been reported before. To test the safety and efficacy of esketamine during DISE in children with OSAHS, we compare esketamine (Group K) with dexmedetomidine (Group D) in this study. Methods: 100 children with ASA Ⅰ～Ⅱ grade, prepared for an elective adenotonsillectomy under general anesthesia, were enrolled in this study and randomized into two groups. Midazolam 0.1 mg/kg was administered intravenously for both groups. In Group D a 1μg/kg bolus of dexmedetomidine was given over 10 min followed by the infusion rate 1μg/kg/hr to the end of DISE. Group K received a 1.0 mg/kg IV bolus of esketamine over 10 sec followed by the infusion rate 1mg/kg/hr to the end of DISE. Results: Group K had a higher percentage of success than Group D (p = 0.008). The onset time of Group K was shorter than that of Group D (p<0.001). The University of Michigan Sedation Scale (UMSS) score of Group K was higher than that of Group D (p = 0.005). The risk of adverse effects (AEs) was lower in Group K (p<0.001). In Group D, systolic and diastolic blood pressure (SBP and DBP) and heart rate (HR) all decreased, while in Group K, SBP, DBP and HR hardly changed. Conclusion: Esketamine in comparison to dexmedetomidine provides more effective and safer depth of anesthesia for OSAHS pediatric DISE by ensuring high percentage of success, short onset time, deep sedation, and few AEs.